Some Common Fixed Point on Generalized Cyclic Contraction Mappings with Implicit Relation and Its Applications - Chuensupantharat, Nantaporn; Kumam, Poom (Communications in Mathematics and Applications, 2016)
From the concept of cyclic relation, we introduced the generalized cyclic contraction with respect to multi-valued mappings under implicit relation and obtained some common fixed point theorem in complete metric spaces. In addition, some examples and applications are presented to demonstrate our results.